An overview of rotavirus vaccination programs in developing countries. (2nd June 2020) - Hallowell, Benjamin D.; Tate, Jacqueline; Parashar, Umesh
ABSTRACT: Introduction: Rotavirus is the leading cause of acute diarrhea among children <5 years worldwide. As all children are equally susceptible to infection and disease development, rotavirus vaccination programs are the best upstream approach to preventing rotavirus disease, and the subsequent risk of hospitalization or death. Areas covered: We provide an overview of global rotavirus vaccine policy, summarize the burden of rotavirus disease in developing countries, review data on the effectiveness, impact, safety, and the cost-effectiveness of rotavirus vaccination programs, and identify areas for further research and improvement. Expert opinion: Rotavirus vaccines continue to be an effective, safe, and cost-effective solution to preventing rotavirus disease. As two new rotavirus vaccines enter the market (Rotasiil and Rotavac) and Asian countries continue to introduce rotavirus vaccines into their national immunization programs, documenting vaccine safety, effectiveness, and impact in these settings will be paramount.